MDER: método de desenvolvimento enxuto e robusto aplicado à concepção de produtos e seus processos de manufatura a partir do enfoque à fase de design - Felipe Costa Cardoso (2019)
The globalized market has extended broad competition beyond any physical frontier. The imminent trade opening between Brazil and the North American and European markets may still strongly transform the competitive landscape in our market. Brazilian companies need to compete with Chinese, American, European products that are extremely competitive in quality and price in the national soil. This fact exemplifies the current competitive scenario in which companies are immersed and justifies the efforts made in this context. Economic sustainability is directly linked to the ability to be efficient in delivering products, ensuring quality at the right price and on time that the market expects. Despite these efforts, much of the market suffers from inefficient project development methods, which result in high waste and consequent lack of competitiveness for the industry. Advances in the area of project methodology have led to the creation of several methods that are now available to companies, however, they have specific and little comprehensive benefits. This means that none of them are able to concentrate in a single method several benefits in a lean and robust design development process. Given this fact, the present work proposes a design development method (MDER) capable of guaranteeing the robustness of a product and its manufacturing process by emphasizing the design conception and development phase. MDER also innovates in proposing a tool called MQ-DFMA that can objectively evaluate the quality of product design from the perspective of manufacturing and assembly, and is customizable to the institution that implements it. In addition, the method proposed by this work prescribes structures that allow discernment between critical and non-critical product designs, where different paths for such design peculiarities are defined in order to ensure robust development at the best possible design cost. A case study is presented where an economic feasibility assessment of the application of MDER in an automotive company is performed. This case study presents economic data that indicate greater efficiency of the proposed method when compared to a method already present in the market. That said, the author intends the present dissertation to generate content that helps in the process of developing projects of companies, institutions and even academy, in a more competitive and sustainable way.